International Arbitration in a Global Economy: The Challenges of the Future - Hanotiau, Bernard (Institutional Knowledge at Singapore Management University, 2010)
The forces of globalization have generated an increased number of international contracts, generating themselves an enormous increase in complex commercial disputes. They have fueled the development of international arbitration as the preferred choice of businessmen for the resolution of their disputes. They have further led to a denationalization of arbitration, both procedurally and substantively, as well as to a convergence of national legislation and institutional rules, based on a consensus on a greater liberalization of the process. The forces of globalization have also opened the door to the application by arbitral tribunals of general principles of international commercial law, common to all nations, and have contributed to the development of an international arbitration culture. Beyond its success, international arbitration is facing today many challenges. There is an increased concern over its judicialization, its time and cost efficiency and various ethical issues. What can be done to overcome these challenges and make sure that arbitration will continue to offer the qualities and advantages that have been the keys of its success?